AB0794 Effect of tofacitinib on patient-reported outcomes in patients with active psoriatic arthritis: results from two phase 3 studies. (15th June 2017) - Strand, V; Vlam, K de; Covarrubias-Cobos, JA; Mease, PJ; Gladman, DD; Hendrikx, T; Kudlacz, E; Graham, D; Wu, J; Chen, L
Abstract : Background: Tofacitinib is an oral Janus kinase inhibitor under investigation for treatment of psoriatic arthritis (PsA). The safety and efficacy of tofacitinib for the treatment of PsA has been investigated in two Phase 3 randomised controlled trials (RCTs: OPAL Broaden [12 months; NCT01877668 ]; OPAL Beyond [6 months; NCT01882439 ]). Objectives: To evaluate patient-reported outcomes (PROs) in patients (pts) with active PsA enrolled in OPAL Broaden (N=422) and OPAL Beyond (N=394). OPAL Broaden pts had an inadequate response (IR) to ≥1 conventional synthetic disease-modifying antirheumatic drug and were naïve to tumour necrosis factor inhibitors (TNFi) whilst OPAL Beyond pts had an IR to ≥1 TNFi. Methods: Pts were randomised to tofacitinib 5 mg twice daily (BID), tofacitinib 10 mg BID, placebo (PBO)→ tofacitinib 5 mg BID, PBO→ tofacitinib 10 mg BID and, in OPAL Broaden, also to adalimumab 40 mg subcutaneously every two weeks (active comparator). Pts receiving PBO advanced to either tofacitinib 5 mg BID or 10 mg BID at month 3 (M3) in both RCTs. Least squares mean changes from baseline in: Patient's Global Assessment of Arthritis (PtGA; Visual Analogue Scale [VAS]); Arthritis Pain (Pain; VAS); Short Form-36 Health Survey (SF-36); Functional Assessment of Chronic Illness Therapy–Fatigue (FACIT-F); Dermatology Life Quality Index (DLQI) and Ankylosing Spondylitis Quality of Life (ASQOL) questionnaires are reported. Nominal p values are reported without adjustments for multiple comparisons. Results: Patients with active PsA in OPAL Broaden and OPAL Beyond RCTs receiving tofacitinib 5 mg and 10 mg BID reported improved PROs compared with PBO (Table 1 ). Greater improvements in PtGA and Arthritis Pain were observed as early as Week 2 through M3 with both tofacitinib doses compared with PBO in both studies (p≤0.05). Greater improvements were also reported in SF-36 Physical Component Summary, DLQI and ASQOL scores at M1 and M3 with both tofacitinib doses compared with PBO (p≤0.05). There were greater improvements in SF-36 physical functioning, bodily pain and vitality domains with both tofacitinib doses compared with PBO in both studies (p≤0.05) at M3. SF-36 social functioning domain showed greater improvement with tofacitinib 5 mg BID in OPAL Broaden and both tofacitinib doses in OPAL Beyond compared with PBO at M3 (p≤0.05). SF-36 role-physical domain showed greater improvement with tofacitinib 10 mg BID in OPAL Beyond at M3 compared with PBO (p≤0.05). FACIT-F showed a greater improvement in both studies at M3 with both tofacitinib doses compared with PBO (p≤0.05). In OPAL Broaden, improvements in PROs were similar between tofacitinib and adalimumab. Conclusions: Pts with active PsA receiving tofacitinib reported greater improvements in PROs compared with PBO at M3 that were maintained throughout both RCTs. Acknowledgements: To be presented at AAD 2017 and reproduced with permission. This study was sponsored by Pfizer Inc. Editorial support was provided by S. Morgan of CMC and was funded by Pfizer Inc. Disclosure of Interest: V. Strand Consultant for: AbbVie, Amgen, Bristol-Myers Squibb, CORRONA, Eli Lilly, Janssen, Novartis, Pfizer Inc, UCB, K. de Vlam Consultant for: Celgene, Eli Lilly, Janssen, Novartis, Pfizer Inc, UCB, Speakers bureau: Celgene, Eli Lilly, Janssen, J. Covarrubias-Cobos Grant/research support from: Bristol-Myers Squibb, Eli Lilly, Janssen, Pfizer Inc, P. Mease Grant/research support from: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Eli Lilly, Janssen, Novartis, Pfizer Inc, Sun, UCB, Consultant for: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Crescendo, CORRONA, Dermira, Janssen, Eli Lilly, Merck, Novartis, Pfizer Inc, Sun, UCB, Zynerba, Speakers bureau: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Crescendo, Genentech, Janssen, Novartis, Pfizer Inc, UCB, D. D. Gladman Grant/research support from: Amgen, AbbVie, Bristol-Myers Squibb, Celgene, Janssen, Eli Lilly, Pfizer Inc, Novartis, UCB, Consultant for: Amgen, AbbVie, Bristol-Myers Squibb, Celgene, Janssen, Eli Lilly, Pfizer Inc, Novartis, UCB, Speakers bureau: Amgen; AbbVie; Bristol-Myers Squibb; Celgene; Janssen; Eli Lilly; Pfizer Inc; Novartis; UCB, T. Hendrikx Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, E. Kudlacz Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, D. Graham Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, J. Wu Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, L. Chen Shareholder of: Pfizer Inc, Employee of: Pfizer Inc